2015
DOI: 10.1080/1369183x.2015.1082286
|View full text |Cite
|
Sign up to set email alerts
|

Friends or foes? Migrants and sub-state nationalists in Europe

Abstract: How do sub-state nationalists respond to the growing presence of cultural diversity in their 'homelands' resulting from migration? Sub-state nationalists in Europe, in 'nations without states' such as Catalonia and Scotland, have been challenging the traditional nation-state model for many decades. While the arguments in favour of autonomy or independence levelled by these movements have become more complex, sub-state nationalist movements remain grounded by their perceived national community that is distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…As stated in the introductory contribution to this volume (Jeram, van der Zwet, and Wisthaler 2015), the contradiction between increasingly culturally heterogeneous identities and sustained support for nationalism is particularly relevant for SNRPs. National identity is one of the key reference points for SNRP politics.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As stated in the introductory contribution to this volume (Jeram, van der Zwet, and Wisthaler 2015), the contradiction between increasingly culturally heterogeneous identities and sustained support for nationalism is particularly relevant for SNRPs. National identity is one of the key reference points for SNRP politics.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The clusters of factors that explain the positioning of old minorities towards migration relate to demography, history, the economy, linguistic and cultural barriers, party landscape and electoral system as well as policy control over immigration (Hepburn 2014: 52-57, Shafir 1995, Medda-Windischer-Carlà 2015, Medda-Windischer-Popelier 2016, Jeram-van der Zwet-Wisthaler 2015. Some of these factors are locally rooted.…”
Section: Cluster Of Factors Influencing the Relationship Migration/sumentioning
confidence: 99%
“…In this respect, it is crucial to stress that opportunities should not be easily converted into obligations. A preference for a 'persuasion and argument' model over a 'sanction and force' model is in fact to be supported (Jeram-van der Zwet-Wisthaler 2015, Baycan 2016. In Belgium, for instance, rigid language regimes established to protect the Dutch language against francophone linguistic dominance risk being perceived as obstacles to a polyethnic society (Medda-Windischer-Popelier 2016b).…”
Section: Participation and Equality In Diversitymentioning
confidence: 99%
“…Many policy areas relevant to immigrant integration, such as education, housing, social services and language, are, at least partially, shared between the central state and Spain's seventeen ACs (Autonomous Communities). In the Basque Country and Catalonia, immigrant integration intersects with matters of national identity because most newcomers are likely to adopt the majority Castilian Spanish language and culture which may compromise the goals of sub‐state nationalism in the long run (Jeram, ; Jeram et al., ).…”
Section: Immigration and Interculturalism In Spainmentioning
confidence: 99%
“…Recent scholarship focusing on integration discourse in sub‐state nations has revealed that most stateless nationalist and regionalist parties (SNRPs) have not jumped on the anti‐multiculturalism bandwagon (Barker, ; Hepburn, ; Jeram et al., ). SNRPs are important to the politics of multinational states since they form governments in regional parliaments and often wield influence in state‐level politics (Lecours, ).…”
Section: Introductionmentioning
confidence: 99%